Basal Insulin Dose Titration for Glycemic Control in Patients With Type 2 Diabetes Mellitus in Thailand: Results of the REWARDS Real-World Study. (July 2020) - Deerochanawong, Chaicharn; Leelawattana, Rattana; Kosachunhanun, Natapong; Tantiwong, Puntip
This multicenter, longitudinal, descriptive, observational study of T2DM adults in Thailand aimed to assess real-world outcomes of basal insulin (BI) dose titration on glycemic control. Three-hundred and twenty-four patients were recruited and followed up over 24 weeks. Basal insulin titration was physician-driven in 58.2% of patients and patient-driven in the rest. During the 24-week study period, the total daily BI dose moved from 20.9 to 25.6 in the physician-driven group, while in the patient-driven group, it increased from 25.3 to 29.7. Thirty-five patients (11.2%) achieved their individualized HbA1c targets, with 18 patients (5.8%) achieving HbA1c ⩽ 7% without documented hypoglycemia. In summary, this study highlights that BI titration is suboptimal in the real world, and patients are unable to achieve their glycemic targets.